Competitiveness and the Evolution of the Real Exchange Rate in Chile - Guerguil, Martine; Kaufman, Martin (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews the evolution of certain price and nonprice competitiveness indicators in Chile and concludes that the pecuniary loss of competitiveness associated with the appreciation of the peso since the late 1980s has been broadly offset by productivity gains and adjustments in factor intensity, particularly in the manufacturing sector. However, there may be limited room for further advances from that point, which gives new prominence to certain policy issues such as structural reforms to increase productivity, a reassessment of the tax treatment of the mining sector, and a rebalancing of the macroeconomic policy mix to dampen speculative capital inflows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet